2016
DOI: 10.18632/oncotarget.10459
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin co-treatment enhances tamoxifen cytotoxicity in luminal A breast tumor cells by facilitating lysosomal degradation of receptor tyrosine kinases

Abstract: Luminal A breast cancer is the most common breast cancer subtype which is usually treated with selective estrogen receptor modulators (SERMS) like tamoxifen. Nevertheless, one third of estrogen receptor positive breast cancer patients initially do not respond to endocrine therapy and about 40% of luminal A breast tumors recur in five years. In this study, we investigated an alternative treatment approach by combining tamoxifen and salinomycin in luminal A breast cancer cell lines. We have found that salinomyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…that salinomycin potentiated cytotoxicity effect of tamoxifen by increasing caspase 3/7 activation in MCF‐7 cells. Moreover, our finding also are consistent with Sommer et al . which indicated the combination of salinomycin increased tamoxifen sensitivity in MCF‐7 cells via assisting lysosomal degradation of tyrosine kinase receptors.…”
Section: Discussionsupporting
confidence: 92%
“…that salinomycin potentiated cytotoxicity effect of tamoxifen by increasing caspase 3/7 activation in MCF‐7 cells. Moreover, our finding also are consistent with Sommer et al . which indicated the combination of salinomycin increased tamoxifen sensitivity in MCF‐7 cells via assisting lysosomal degradation of tyrosine kinase receptors.…”
Section: Discussionsupporting
confidence: 92%
“…SAL has been shown to inhibit CSCs in various cancer types; several studies have indicated that SAL combined with chemotherapeutic drugs, such as doxorubicin, tamoxifen, and cisplatin, enables synergistic anticancer activity in gastric cancer, breast cancer, and cholangiocarcinoma. 39 41 However, SAL possesses poor aqueous solubility and unfavorable properties in terms of toxicity. Thus, to overcome these disadvantages, nanoparticles have been used to deliver SAL.…”
Section: Discussionmentioning
confidence: 99%
“…One such mechanism is intrinsic drug resistance; this means that tumor cells are resistant to the applied drug from the beginning of treatment. The other mechanism is acquired resistance, wherein tumor cells develop resistance to the applied drug following an initial response ( 50 ). In the present study, it was observed that in MEA A, for example, five times-treated cells exhibited the same sensitivity to DXR as untreated cells.…”
Section: Discussionmentioning
confidence: 99%